Current Guidelines on Antithrombotic Management in Patients Undergoing Gastrointestinal Endoscopy - Muhammad Begawan Bestari; Bayu Laksono (Acta Medica Indonesiana, 2019)
Endoscopic procedure is commonly used to make diagnosis or therapy. Endoscopy has risk on the procedure or after the procedure. Patient with antithrombotic therapy, both antiplatelet and/or anticoagulant, for underlying diseases has higher risk for bleeding and thromboembolic events in this procedure. The physician should consider risk and benefit for adjusting the antithrombotic therapy, in addition to minimize bleeding and thromboembolic events. For low risk procedure, adjustments in antithrombotic therapy usually not necessarily needed. For high risk procedure, there are several adjustments based on the type of medication and patient’s condition in specific. European Society of Gastrointestinal Guidelines Endoscopy (ESGE) and British Society of Gastrointestinal (BSG); American Society of Gastrointestinal Endoscopy (ASGE); and lastly Asian Pacific Association of Gastroenterology (APAGE) and Asian Pacific Society for Digestive Endoscopy (APSDE) have published guidelines to help physician to make decisions regarding antithrombotic therapy management during endoscopy. This article compares and contrasts the approach of each guideline, in design to help the decision-making process. However, each patient’s clinical condition may differ from one to another and should be considered carefully in making a final decision.